The Dynamics of Keroncong Music in Indonesia, 1940âs â 2000âs - Sunarti, Linda; Triwinarti, Wiwin (TAWARIKH, 2013)
ABSTRACT: âKeroncongâ music, as a treasure of Indonesian national music, has been experiencing a long phase since the arrival of the Moorish as Portuguese slaves to Indonesia in the 16th century. In the long period, the âkeroncongâ music then, as other kinds of traditional music, has to face industry music, especially Western music. The power of financial capital, the superiority of technology, and the sophistication of marketing ground down traditional music. This paper tries to analyze the âkeroncongâ music in Indonesia that can still be maintained or popularized through various ways and by making a proper media of promotion such as through television and radio so that society are familiar to âkeroncongâ music. Therefore, âkeroncongâ artists should make innovations or changes that can attract peopleâs interest to âkeroncongâ music. They should create song lyrics that reflec the life of society or take themes that is in accordance to their period. Although there are many new âkeroncongâ compositions, but the new âkeroncongâ songs are rarely published in media. The emergence of âcampursariâ in the 1990s, pioneered by Manthous, brought a power of interest and became a magnet for fans and activists of âkeroncongâ and traditional music so that they appreciate the music and many groups of âcampursariâ music which is rooted from âkeroncongâ grew. The same effort was done by Didi Kempot and Koko Thole who has given new colour to âkeroncongâ music. They made efforts to spread âkeroncongâ music to a wide range of society and also develop the music itself.Â Â Â  Â Â KEY WORDS: âKeroncongâ music, time of revolution, Indonesian society, âcampursariâ music, and innovations in traditional music.Â Â Â About the Authors: Linda Sunarti, M.Hum. and Wiwin Triwinarti, M.A. are Lecturers at the Department of History, Faculty of Humanities UI (University of Indonesia), UI Campus Depok, West Java, Indonesia. Corresponding author is lindsayrani@yahoo.co.ukHow to cite this article? Sunarti, Linda & Wiwin Triwinarti. (2013). âThe Dynamics of Keroncong Music in Indonesia, 1940âs â 2000âsâ in TAWARIKH: International Journal for Historical Studies, Vol.5(1) October, pp.91-102. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (August 3, 2013); Revised (September 7, 2013); and Published (October 28, 2013).